(untitled) (Journal of Partial Differential Equations, 1991)
Consider the degenerate parabolic equation (porous medium equation with gravity term): u_t = (u^m)_xx + (u^n)_x, -&#8734 < x < &#8734, t > 0, m > 1 u(x, 0) = u_0(x), -&#8734 < x < &#8734 The main results consist of the estimation of t^&#8727_i called waiting time, the behavior of pressure V = mm-1u^m-1 near a vertical or a nonvertical part of &#962_i(t) and a condition of that &#962_i(t) is continuously differentiable.